1995
DOI: 10.1007/bf03015097
|View full text |Cite
|
Sign up to set email alerts
|

Thiopentone pretreatment for propofol injection pain in ambulatory patients

Abstract: This study investigated propofol injection pain in patients undergoing ambulatory anaesthesia. In a randomized, double-blind trial, 90 women were allocated to receive one of three treatments prior to induction of anaesthesia with propofol. Patients in Group C received 2 ml normal saline, Group L, 2 ml, lidocaine 2% (40 mg) and Group T, 2 ml thiopentone 2.5% (50 mg). Venous discomfort was assessed with a visual analogue scale (VAS) 5-15 sec after commencing propofol administration using an infusion pump (rate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
(2 reference statements)
0
18
0
1
Order By: Relevance
“…[68][69][70]102 If necessary, the drug product labeling may include a recommendation that a specific vehicle or local anesthetic or other protective agent be administered concurrently with the drug. 40,41,43,45,47,57,66,[76][77][78][79]82,83,[87][88][89]91,[93][94][95]100,101,107,108,116,121 The addition of compounds such as procaine or lidocaine to an injection will block the transmission and perception of pain (see mediation of pain) associated with injection via their action on sodium receptors. However, the question that needs to be addressed is whether this is a desirable to utilize this multiple drug approach for long-term therapy.…”
Section: Methods To Reduce or Eliminate Pain On Injectionmentioning
confidence: 99%
“…[68][69][70]102 If necessary, the drug product labeling may include a recommendation that a specific vehicle or local anesthetic or other protective agent be administered concurrently with the drug. 40,41,43,45,47,57,66,[76][77][78][79]82,83,[87][88][89]91,[93][94][95]100,101,107,108,116,121 The addition of compounds such as procaine or lidocaine to an injection will block the transmission and perception of pain (see mediation of pain) associated with injection via their action on sodium receptors. However, the question that needs to be addressed is whether this is a desirable to utilize this multiple drug approach for long-term therapy.…”
Section: Methods To Reduce or Eliminate Pain On Injectionmentioning
confidence: 99%
“…Adult studies using thiopentone demonstrated that pretreating a vein with 50 mg of thiopentone prior to propofol injection was not as efficacious in reducing injection pain as 40 mg of lidocaine. 7 In contrast, pretreating with 100 mg thiopentone was more effective than 20 mg of lidocaine. 8 In children, pretreatment with 3 mg·kg -1 of thiopentone prior to injecting propofol 1.5 mg·kg -1 with lidocaine 0.075 mg·kg -1 reduced the injection pain from 81% to 27%.…”
Section: Méthode : L'approbation Dumentioning
confidence: 95%
“…Nevertheless, the sedative effect of such a large dose of thiopental on perception of pain by visual analogue scale cannot be eliminated. Haugen et al (14) compared the efficacy of thiopental 50 mg. (approx. 0.8 mg/kg) pretreatment with lidocaine 40 mg and observed that thiopental only reduced the severity of propofol pain whereas lidocaine reduced both the incidence and severity of pain.…”
Section: Discussionmentioning
confidence: 99%